Method for preparing graded porous nickel electrode through step-by-step dealloying and application of graded porous nickel electrode

The preparation of graded porous nickel electrodes on a nickel-based substrate by step-by-step dealloyization method solves the problems of complex preparation processes and poor stability in the prior art, and achieves efficient catalytic performance and long-term operation stability.

CN119663338APending Publication Date: 2025-03-21BAOSHILAI NEW MATERIAL TECHNOLOGY (SUZHOU) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411939655.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing step-by-step porous electrode preparation process is complex, the load-bearing capacity is reduced after long-term use, the catalyst layer is prone to fall off, and the adhesion strength between layers is low.

Method used

The step-by-step dealloyization method is used to prepare a graded porous nickel electrode, including spraying nickel-aluminum material on a nickel-based substrate, performing heat treatment, and performing step-by-step activation in different concentrations of alkali liquid, gradually reducing the concentration and activation temperature of alkali liquid.

Benefits of technology

The construction of a hierarchical porous structure is realized, which improves the interlayer bonding strength and stability of the electrode, reduces the complexity of the preparation process, and extends the service life of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663338A_ABST
    Figure CN119663338A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a graded porous nickel electrode by step-by-step dealloying and application thereof, and the method comprises the following steps: spraying a nickel-aluminum material on a nickel-based substrate to obtain a first intermediate product; performing heat treatment on the first intermediate product to obtain a second intermediate product; the second intermediate product is sequentially placed in alkali liquor with different concentrations for step-by-step activation, and the graded porous nickel electrode is obtained; in the step of step-by-step activation, the concentration of the alkali liquor is gradually reduced, and the activation temperature is gradually reduced. According to the graded porous nickel electrode, the efficient mass transfer rate and catalytic efficiency are guaranteed; the bonding strength between the coating and the substrate is high, the interlayer structure is stable, the mechanical property and stability are good, and the service life is long; and the hierarchical porous structure can be constructed only through step-by-step activation, so that the preparation process is remarkably simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of alkaline water electrolysis, and specifically relates to a method for preparing a graded porous nickel electrode by step-by-step dealloying and its application. Background Art

[0002] Hydrogen production by water electrolysis can directly use direct current to dissociate water into oxygen (anode) and hydrogen (cathode), with zero carbon consumption and generation throughout the process, which is the future development direction of the energy industry. Currently, most of the electrodes widely used in water electrolysis are prepared by spraying, electroplating, chemical plating and other methods, and have a single pore structure. Among them, the electrode with a single-stage large pore structure has the problem of small active sites, which is difficult to meet the requirements of electrocatalytic efficiency; while the electrode with a single-stage small pore structure is not conducive to gas transmission, has poor gas repellency, and causes bubble blocking effect. The blockage of bubbles further leads to an increase in internal pressure, causing the catalyst to fall off, reducing the stability of the electrode. In addition, the attachment of bubbles will reduce the electroactive sites and increase the resistance.

[0003] In order to avoid the problems existing in single-stage large-pore electrodes and single-stage small-pore electrodes, graded porous electrodes with both large and small pores are currently the main research direction. However, the existing graded porous electrodes are mainly prepared by adhesives, mechanical bonding, step-by-step electrodeposition, etc., wherein adhesives or mechanical bonding methods combine a variety of porous materials with different characteristics together, the preparation process is complicated, and long-term use will lead to a decrease in the carrying capacity of the gradient porous material and easy detachment of the catalyst layer; the graded porous material prepared by the step-by-step electrodeposition method has the problem of low bonding strength between layers, and the waste electrolyte is difficult to handle, the preparation process is complicated, and the coating thickness is uneven. Summary of the invention

[0004] The purpose of the present application is to provide a method for preparing graded porous nickel electrodes by step-by-step dealloying and its application, so as to solve the problems of graded porous electrodes in the prior art, such as complex preparation process, reduced carrying capacity after long-term use, easy detachment of catalyst layer, and low bonding strength between layers.

[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides a method for preparing a graded porous nickel electrode by step-by-step dealloying, comprising: Spraying a nickel-aluminum material on a nickel-based substrate to prepare a nickel-aluminum coating on the surface of the nickel-based substrate to obtain a first intermediate product; thermally treating the first intermediate product to obtain a second intermediate product; placing the second intermediate product in alkaline solutions of different concentrations in sequence for step-by-step activation to obtain a graded porous nickel electrode; Wherein, in the step-by-step activation, the concentration of the alkali solution is gradually reduced, and the activation temperature is gradually reduced.

[0006] In one or more embodiments, the steps of the stepwise activation are specifically: placing the second intermediate product in a first alkali solution for a first activation to obtain a third intermediate product; placing the third intermediate product in a second alkaline solution for a second activation to obtain a graded porous nickel electrode; Wherein, the concentration of the first alkali solution is greater than the concentration of the second alkali solution, and the activation temperature of the first activation is higher than the activation temperature of the second activation.

[0007] In one or more embodiments, the first alkali solution comprises 23-40 wt % sodium hydroxide solution, the activation temperature of the first activation is 60-100° C., and the activation time is 0-2 h; The second alkali solution includes 4-22wt% sodium hydroxide solution, the activation temperature of the second activation is 30-60°C, and the activation time is 8-24h.

[0008] In one or more embodiments, the first alkali solution and the second alkali solution further comprise 1-8 wt % of an additive, wherein the additive comprises one or more combinations of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium gluconate, sodium citrate, and sodium tartrate.

[0009] In one or more embodiments, the step of spraying the nickel-aluminum material on the nickel-based substrate is specifically: A plasma spraying process is adopted to spray the nickel-aluminum material on the nickel-based substrate using nickel-coated aluminum powder as spraying powder.

[0010] In one or more embodiments, the thickness of the nickel-aluminum coating is 40-50 μm.

[0011] In one or more embodiments, the step of spraying the nickel-aluminum material on the nickel-based substrate further includes: The surface of the nickel-based substrate is roughened by sandblasting.

[0012] In one or more embodiments, the step of heat treating the first intermediate product is specifically: The first intermediate product is placed in a hydrogen environment, heat treated at 550-650° C. for 1-2 hours, and then cooled to room temperature at a rate of 3-5° C. / min.

[0013] In order to achieve the above-mentioned purpose, the second aspect of the present application provides a graded porous nickel electrode prepared by the method described in any of the above-mentioned embodiments.

[0014] In order to achieve the above-mentioned purpose, the third aspect of the present application provides an application of the graded porous nickel electrode described in any of the above-mentioned embodiments as a hydrogen evolution electrode in an alkaline water electrolysis reaction.

[0015] Different from the prior art, the beneficial effects of this application are: The hierarchical porous nickel electrode of the present application has a multi-scale pore structure from nanometers to micrometers. The micropores and mesopores can provide reaction sites or capillary forces for the catalyst, while the macropores promote the diffusion of gas or fluid through the interconnected skeleton, ensuring efficient mass transfer rate and catalytic efficiency. Compared with the traditional single-stage porous nickel electrode, the hierarchical porous nickel electrode of this application has a -500 mA / cm 2 The overpotential under the condition of 1.5V / cm2 was reduced by 52.4%, and the double-layer capacitance increased by 7.97 times; The hierarchical porous nickel electrode of the present invention has a strong bonding strength between the coating and the substrate, a stable interlayer structure, excellent mechanical properties, good stability, and a long service life. 2 After long-term operation for 1000 hours, the overpotential remains basically unchanged; The hierarchical porous nickel electrode of the present application only requires step-by-step activation to achieve the construction of a hierarchical porous structure, which significantly simplifies the preparation process compared to the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 It is a schematic flow chart of an implementation method of the present invention for preparing a graded porous nickel electrode by step-by-step dealloying; Figure 2 yes Figure 1 A schematic flow chart of an implementation method corresponding to S300; Figure 3 is a surface SEM image of the graded porous nickel electrode prepared in Example 2 of the present application; Figure 4 is a cross-sectional SEM image of the graded porous nickel electrode prepared in Example 2 of the present application; Figure 5 : are the LSV curves of the electrodes prepared in Examples 2, 5, 6 and Comparative Examples 3 and 4 of the present application; Figure 6 It is the double-layer capacitance curve of the electrodes prepared in Examples 2, 5, 6 and Comparative Examples 3 and 4 of the present application; Figure 7 It is the stability test curve of the electrodes prepared in Example 2 and Comparative Examples 3 and 4. DETAILED DESCRIPTION

[0018] In order to enable those skilled in the art to better understand the technical solutions in the present application, the technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present application.

[0019] The activity of the commonly used nickel-based catalysts currently comes from the catalytic properties of nickel itself and its porous structure. The pore structure of traditional nickel-based catalysts is single, and the active sites of the single-stage large-pore electrode are small, which is not conducive to improving the catalytic efficiency. The single-stage small-pore electrode has poor gas repellency and has a bubble blocking effect, which easily leads to catalyst shedding and increased resistance, and low utilization of active sites.

[0020] Compared with nickel-based catalysts with a single pore structure, hierarchical porous nickel-based catalysts not only have a higher specific surface area to ensure catalytic efficiency, but also have sufficient bubble transmission channels to reduce the contact area between bubbles and electrodes, accelerate bubble shedding, and increase the service life of nickel-based catalysts. However, due to the limitations of the preparation process, traditional hierarchical porous nickel-based catalysts have problems such as poor interlayer bonding strength, reduced load-bearing capacity after long-term use, and uneven coating thickness, and the preparation process is complicated.

[0021] In order to solve the above problems, the applicant has developed a new method for preparing a graded porous nickel electrode, which can effectively simplify the preparation process, reduce the preparation cost, and significantly improve the interlayer bonding strength of the electrode and increase the service life of the electrode while ensuring the electrode catalytic efficiency.

[0022] Specifically, see Figure 1 , Figure 1 It is a schematic flow chart of an implementation method of the present application for preparing graded porous nickel electrodes by step-by-step dealloying.

[0023] like Figure 1 As shown, the method includes: S100, spraying a nickel-aluminum material on a nickel-based substrate to prepare a nickel-aluminum coating on the surface of the nickel-based substrate to obtain a first intermediate product.

[0024] In one embodiment, the nickel-based substrate may be a nickel mesh. In other embodiments, the nickel-based substrate may also be a substrate material of a conventional nickel electrode such as nickel foam, and both can achieve the effect of this embodiment.

[0025] In one embodiment, the method of spraying the nickel-aluminum material may be to use a plasma spraying process, using a nickel-clad aluminum material as a spraying powder, and spraying the nickel-aluminum material on the surface of a nickel-based substrate.

[0026] Among them, the process parameters of the plasma spraying process and the specific material ratio of the nickel-clad aluminum material are not limited. As long as the spraying of the nickel-aluminum material can be achieved, the effect of the present application can be achieved.

[0027] For example, with 30~50μm Ni 75 Al 25 When nickel-clad aluminum powder is used as spraying powder, the plasma arc power can be 33kW, the nozzle diameter can be 1mm, the spraying distance can be 150mm, the spraying angle can be 60°, and the gas pressure can be 0.4MPa; when other types of nickel-clad aluminum powder are used as raw materials, the plasma spraying parameters can be adjusted accordingly based on the actual working conditions, and the effects of this embodiment can be achieved.

[0028] In one embodiment, the thickness of the nickel-aluminum coating may be 40-50 μm.

[0029] S200, heat-treating the first intermediate product to obtain a second intermediate product.

[0030] It can be understood that a nickel-aluminum coating is deposited on the surface of the nickel-based substrate of the first intermediate product, and after further heat treatment, nickel and aluminum diffuse into each other to form an alloy phase.

[0031] In one embodiment, the heat treatment may specifically be: The first intermediate product is placed in a hydrogen environment, heat treated at 550-650° C. for 1-2 hours, and then cooled to room temperature at a rate of 3-5° C. / min.

[0032] S300, placing the second intermediate product in alkaline solutions of different concentrations in turn for step-by-step activation to obtain a graded porous nickel electrode.

[0033] Among them, in the step-by-step activation process, the concentration of the alkali solution gradually decreases and the activation temperature gradually decreases.

[0034] The present application constructs a hierarchical porous structure through step-by-step activation. Specifically, the concentration of the alkali solution and the activation temperature can be gradually reduced. The second intermediate product is first activated in an alkali solution with a higher concentration and a higher temperature, and then activated in an alkali solution with a lower concentration and a lower temperature. The hierarchical porous structure is constructed through multiple activations.

[0035] There are various nickel-aluminum intermetallic compounds such as Al, NiAl3, Ni2Al3, NiAl, Ni3Al, and Ni in the second intermediate product, which are ranked according to the difficulty of removal in the alkali solution: Al>NiAl3>Ni2Al3>NiAl>Ni3Al; the alkali solution concentration is high, the temperature is high, the corroded area is large, and the corrosion rate is fast, which easily forms large pores in the graded porous structure; the alkali solution concentration is low, the temperature is low, the corroded area is small, and the corrosion rate is fast, which easily forms small pores in the graded porous structure, thus forming a graded porous structure.

[0036] In one embodiment, the step activation can be a two-step activation. Figure 2 , Figure 2 yes Figure 1 A flow chart of an implementation method corresponding to S300 in FIG.

[0037] like Figure 2 As shown, the steps of step-by-step activation include: S301, placing the second intermediate product in a first alkaline solution for a first activation to obtain a third intermediate product.

[0038] S302, placing the third intermediate product in a second alkaline solution for a second activation to obtain a graded porous nickel electrode.

[0039] The concentration of the first alkali solution is greater than that of the second alkali solution, and the activation temperature of the first activation is higher than that of the second activation.

[0040] In one embodiment, the first alkali solution may include 23-40 wt % sodium hydroxide solution, the activation temperature of the first activation may be 60-100° C., and the activation time may be 0-2 h; The second alkali solution may include 4-22 wt % sodium hydroxide solution, the activation temperature of the second activation may be 30-60° C., and the activation time may be 8-24 h.

[0041] In order to ensure activation efficiency and stability, the first alkali solution and the second alkali solution may also include 1-8 wt % of additives, and the additives may include one or more combinations of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium gluconate, sodium citrate, and sodium tartrate.

[0042] Please continue reading Figure 1 , in order to improve the bonding area and adhesion of the nickel-aluminum coating in S100, before S100 it also includes: S10, using a sandblasting process to perform surface roughening treatment on the nickel-based substrate.

[0043] It can be understood that by sandblasting the nickel-based substrate, on the one hand, stains on the surface of the substrate can be removed, and more importantly, on the other hand, the surface of the substrate can have different roughness, thereby increasing the bonding area between the subsequent nickel-aluminum coating and the nickel-based substrate, and improving the adhesion of the nickel-aluminum coating.

[0044] In one embodiment, the sandblasting process may use 80 mesh white corundum, the sandblasting distance may be 120 mm, the sandblasting angle may be 60-90°, and the sandblasting gas pressure may be 0.4 MPa.

[0045] In other embodiments, the parameters of the sandblasting process may be adjusted based on actual working conditions, and the surface roughening of the nickel-based substrate may be achieved, and the effect of the present embodiment may be achieved.

[0046] It should be noted that the above steps realize the construction of a hierarchical porous structure through two-step activation. In other embodiments, the number of activations can also be adjusted based on actual working conditions, for example, three-step activation, four-step activation, etc., and the alkali solution concentration and activation temperature of each activation can also be adjusted accordingly based on actual needs, which can achieve the effect of this embodiment.

[0047] It can be understood that since different pore structures are prepared by step-by-step activation of the same coating, the graded porous nickel electrode prepared by the above-mentioned embodiments has a stable interlayer structure, excellent mechanical properties, good stability and long service life; in addition, an exothermic reaction occurs between nickel and aluminum during the thermal spraying process of the nickel-aluminum material, which can still last for 0.003~0.005s after the powder reaches the surface of the substrate, thereby generating a strong micrometallurgical bonding effect between the coating and the substrate. Therefore, the surface catalyst layer of the graded porous nickel electrode of the present application also has a strong bonding strength with the substrate.

[0048] The electrodes prepared in the above embodiments have a multi-scale porous structure from nanometers to micrometers. The micropores and mesopores can provide reaction sites or capillary forces for the catalyst, while the macropores promote the diffusion of gas or fluid through the interconnected skeleton, ensuring efficient mass transfer rate and catalytic efficiency. In particular, the above method only requires step-by-step activation to achieve the construction of a hierarchical porous structure, which significantly simplifies the preparation process compared to the prior art.

[0049] The effects of the technical solution of the present application are further elaborated in detail below in conjunction with specific embodiments.

[0050] Embodiment 1:

[0051] A hierarchical porous nickel electrode is prepared by the following steps: Step 1: Take a 160 mm × 160 mm nickel mesh as the nickel-based substrate, and use sandblasting technology to roughen the surface of the nickel-based substrate. The sandblasting uses 80 mesh white corundum, the sandblasting distance is 120 mm, the sandblasting angle is 70°, and the sandblasting gas pressure is 0.4 MPa; Step 2: Ni with a particle size of 30~50μm 75 Al 25 Nickel-coated aluminum powder was used as spray powder, and the nickel-aluminum material was sprayed on the nickel-based substrate by plasma spraying process to form a nickel-aluminum coating with a thickness of 50 μm, wherein the plasma arc power was 33 kW, the nozzle diameter was 1 mm, the spraying distance was 150 mm, the spraying angle was 60°, and the gas pressure was 0.4 MPa; Step 3: The sprayed nickel-based substrate is placed in a hydrogen environment for heat treatment at a temperature of 610°C for 1 hour, and then cooled to room temperature at a rate of 3°C / min; Step 4: placing the nickel-based substrate in a first alkaline solution and activating it at 90 °C for 0.5 h; then placing the nickel-based substrate in a second alkaline solution and activating it at 60 °C for 8 h, taking it out, rinsing it and drying it to obtain a graded porous nickel electrode; The first alkali solution is a 30 wt % sodium hydroxide solution, and includes 3 wt % sodium dodecyl sulfate; the second alkali solution is an 18 wt % sodium hydroxide solution, and includes 3 wt % sodium dodecyl sulfate.

[0052] Examples 2 to 10 and Comparative Examples 1 to 2: A graded porous nickel electrode, the preparation method is basically the same as that of Example 1, the only difference is: the concentration of the first alkali solution and the second alkali solution and the additives, the activation temperature and time, and the thickness of the nickel-aluminum coating.

[0053] The parameters of each embodiment and comparative example can be found in the following table.

[0054] Comparative Example 3: A single-stage porous nickel electrode, the preparation method is basically the same as that of Example 1, except that: The nickel-based substrate of Comparative Example 3 was activated only once, the activated alkali solution was a 30 wt % sodium hydroxide solution including 5 wt % sodium tartrate, the activation temperature was 80 ° C, and the activation time was 12 h.

[0055] Comparative Example 4: A single-stage porous nickel electrode, the preparation method is basically the same as that of Example 1, except that: The nickel-based substrate of Comparative Example 4 was activated only once, the activated alkali solution was a 20 wt % sodium hydroxide solution including 5 wt % sodium tartrate, the activation temperature was 60 ° C, and the activation time was 12 h.

[0056] The parameters of the preparation methods of the above embodiments and comparative examples can be found in the following table:

[0057] Effect Example 1: Characterization Analysis The surface and cross-sectional characterization analysis of the graded porous nickel electrode prepared in Example 2 revealed Figure 3 and Figure 4 , Figure 3 This is a surface SEM image of the graded porous nickel electrode prepared in Example 2 of the present application, with a magnification of 2000 times; Figure 4 This is a cross-sectional SEM image of the graded porous nickel electrode prepared in Example 2 of the present application, with a magnification of 1000 times.

[0058] like Figure 3 and Figure 4 As shown, the graded porous nickel electrode prepared in Example 2 has a multi-scale porous structure with macropores located in the outer layer and mesopores located in the inner layer.

[0059] The above data show that Example 2 successfully prepared an electrode with a hierarchical porous structure.

[0060] Effect Example 2: Electrochemical Performance Analysis The LSV curves of the electrodes prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were tested in a 30 wt % KOH solution at 80 ° C using a Bio-Logic electrochemical workstation and a saturated calomel reference electrode, and the current density was calculated to be 500 mA / cm 2 The overpotential under the conditions, and the double-layer capacitance of the electrodes prepared in Examples 1 to 10 and Comparative Examples 1 to 4 was calculated by changing the scanning rate, and the following table data was obtained: Figure 5 and Figure 6 , Figure 5 is the LSV curve of the electrodes prepared in Examples 2, 5, 6 and Comparative Examples 3 and 4 of the present application, Figure 6 It is the double layer capacitance curve of the electrodes prepared in Examples 2, 5, 6 and Comparative Examples 3 and 4 of the present application.

[0061]

[0062] like Figure 5 As shown, the hierarchical porous nickel electrodes prepared in Examples 2, 5, and 6 have significantly lower overpotentials than the single-stage porous nickel electrodes in Comparative Examples 3 and 4, and have more excellent catalytic performance.

[0063] As shown in the table above, the graded porous nickel electrodes prepared in Examples 1 to 10 are -500 mA / cm 2The overpotential under the conditions is significantly lower than that of Comparative Examples 1 to 4, wherein the overpotential of Example 2 is as low as -138 mV, which is 52.4% lower than that of the single-stage porous nickel electrode of Comparative Example 4.

[0064] In addition, in Comparative Example 1, the activation time of the second activation was too short, which affected the construction of the small pore structure and thus the catalytic performance; in Comparative Example 2, the temperature of the first activation was too low, which affected the construction of the large pore structure and thus the catalytic performance.

[0065] The electrochemically active area (ECSA) is proportional to the double layer capacitance, such as Figure 6 As shown, the double-layer capacitance of the hierarchical porous nickel electrodes prepared in Examples 2, 5 and 6 is significantly improved compared with the single-stage porous nickel electrodes in Comparative Examples 3 and 4.

[0066] As shown in the above table, the double-layer capacitance of the graded porous nickel electrodes prepared in Examples 1 to 10 is significantly higher than that in Comparative Examples 1 to 4, among which the double-layer capacitance of the electrode in Example 2 reaches 62.71 μF / cm 2 , which is 8.97 times that of the single-stage porous nickel electrode in Example 3.

[0067] It can be seen from the above data that the graded porous nickel electrode of the present application has a higher active area and stronger catalytic performance than the traditional single-stage porous nickel electrode, which can help reduce the overpotential of the alkaline water electrolysis reaction and increase the hydrogen reaction rate.

[0068] Effect Example 3: Stability Analysis Under the same test conditions as in Example 2, the electrodes prepared in Examples 1 to 10 and Comparative Examples 1 to 4 were tested at -500 mA / cm 2 The stability under current density, the following data and Figure 7 , Figure 7 It is the stability test curve of the electrodes prepared in Example 2 and Comparative Examples 3 and 4.

[0069]

[0070] like Figure 7 As shown, the overpotential of the graded porous nickel electrodes prepared in Examples 2, 5, and 6 remained stable after 1000 h, and the catalytic performance was stable; while the overpotential of the single-stage porous nickel electrodes prepared in Comparative Examples 3 and 4 increased significantly after long-term use, and the catalytic performance decreased.

[0071] As shown in the above table, the overpotential of the graded porous nickel electrodes prepared in Examples 1 to 10 remained basically unchanged after 1000 hours, while the overpotential of the single-stage porous nickel electrodes of Comparative Examples 3 to 4 increased significantly.

[0072] It can be seen from the above data that the graded porous nickel electrode prepared in the present application has good stability and long service life.

[0073] It is obvious to those skilled in the art that the present application is not limited to the details of the exemplary embodiments described above, and that the present application can be implemented in other specific forms without departing from the spirit or essential features of the present application. Therefore, the embodiments should be regarded as exemplary and non-limiting in all respects, and the scope of the present application is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present application. Any reference numeral in a claim should not be regarded as limiting the claim to which it relates.

[0074] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for preparing a graded porous nickel electrode by stepwise dealloying, characterized in that: include: Spraying a nickel-aluminum material on a nickel-based substrate to prepare a nickel-aluminum coating on the surface of the nickel-based substrate to obtain a first intermediate product; thermally treating the first intermediate product to obtain a second intermediate product; placing the second intermediate product in alkaline solutions of different concentrations in sequence for step-by-step activation to obtain a graded porous nickel electrode; Wherein, in the step-by-step activation, the concentration of the alkali solution is gradually reduced, and the activation temperature is gradually reduced.

2. The method according to claim 1, characterized in that The steps of the step-by-step activation are specifically: placing the second intermediate product in a first alkali solution for a first activation to obtain a third intermediate product; placing the third intermediate product in a second alkaline solution for a second activation to obtain a graded porous nickel electrode; Wherein, the concentration of the first alkali solution is greater than the concentration of the second alkali solution, and the activation temperature of the first activation is higher than the activation temperature of the second activation.

3. The method according to claim 2, characterized in that The first alkali solution comprises 23-40wt% sodium hydroxide solution, the activation temperature of the first activation is 60-100°C, and the activation time is 0-2h; The second alkali solution includes 4-22wt% sodium hydroxide solution, the activation temperature of the second activation is 30-60°C, and the activation time is 8-24h.

4. The method according to claim 3, characterized in that The first alkali solution and the second alkali solution further include 1-8 wt % of additives, and the additives include one or more combinations of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, sodium gluconate, sodium citrate, and sodium tartrate.

5. The method according to claim 1, characterized in that The step of spraying the nickel-aluminum material on the nickel-based substrate is specifically as follows: A plasma spraying process is adopted to spray the nickel-aluminum material on the nickel-based substrate using nickel-coated aluminum powder as spraying powder.

6. The method according to claim 1, characterized in that The thickness of the nickel-aluminum coating is 40-50 μm.

7. The method according to claim 1, characterized in that The step of spraying the nickel-aluminum material on the nickel-based substrate also includes: The surface of the nickel-based substrate is roughened by sandblasting.

8. The method according to claim 1, characterized in that The step of heat treating the first intermediate product is specifically: The first intermediate product is placed in a hydrogen environment, heat treated at 550-650° C. for 1-2 hours, and then cooled to room temperature at a rate of 3-5° C. / min.

9. A graded porous nickel electrode prepared by the method according to any one of claims 1 to 8.

10. Use of the graded porous nickel electrode according to claim 9 as a hydrogen evolution electrode in an alkaline water electrolysis reaction.

Citation Information

Cited By

  • Preparation method of graded porous functional coating

    CN121992335A

  • Hierarchical porous nickel electrode and method for preparing the same

    EP4733445A1